Awareness on halal food among consumers in Kuching / Florence Albert - Albert, Florence (2016)
The main objective of this study is to determine the relationship between independent variables and dependent variable. The independent variables consist of exposure on halal food, health conscious and credibility of halal logo. Researcher need to test their hypothesis in order to see the strength of the relationship between both variables. Nowadays, the demand for halal food has showed an increasing because of awareness on clean and good food for their health. Non-Muslim are also those of consumer shows interest in purchasing and consuming the halal food. The quality of the product and the hygienic food are the priority of today's consumer especially in Malaysia as there are many health complication occurs. From the past research, consumer's awareness will increase parallel with the increasing demand of halal food. Media also has played an important role in exposing the important information to the consumer all across Malaysia. This are done through television, radio, the internet, newspaper and other mass media medium. This study can bring benefits to all in order to see the relationship among the variables. Furthermore, this study will influence the consumers in awareness on halal food with the provided information. The SPSS program are used to determine the result through the variety of analysis method.